Evaluating quality of science in CGIAR research programs: Use of bibliometrics - Rünzel, Max; Sarfatti, Paolo.; Negroustoueva, Svetlana (SAGE Publications, 2021)
When evaluating Quality of Science (QoS) in the context of development initiatives, it is essential to define adequate criteria. The objective of this perspective paper is to show how altmetric and bibliometric indicators have been used to support the evaluation of QoS in the 2020 Review of the Phase 2-CGIAR Research Programs (CRPs, 2017–2022), where, for the first time, the Quality of Research for Development (QoR4D) frame of reference has been utilized across the entire CGIAR CRP portfolio. Overall, the CRP review showed a significant output of scientific publications during the period 2017–2020, with 4,872 articles, 220,101 references, and 7.1 citations per article. Additionally, wider interest in scientific publications is demonstrated by good to high altmetrics, with average attention scores ranging from 70.8 to 806.9 with an average of 425.1. The use of selected bibliometrics was shown to be an adequate tool, for use together with other qualitative indicators to evaluate the QoS in the 12 CRPs. The CRP review process clearly demonstrated that standardized, harmonized and consistent data on research output is paramount to provide high-quality quantitative instruments and should be a priority throughout the transition toward One CGIAR. Therefore, we conclude that the QoR4D framework should be augmented by standardized bibliometric indicators embedded in measurement frameworks within the new One CGIAR. Finally, its practical utilization in monitoring and evaluation should be supported with clear guidelines.